2015
DOI: 10.5812/ircmj.11602
|View full text |Cite
|
Sign up to set email alerts
|

Project Management of Randomized Clinical Trials: A Narrative Review

Abstract: Context:A well-structured protocol for a clinical trial may be able to answer clinical questions, but it cannot be deemed enough to ensure success in the face of incompetent management of time as well as human and economic resources. To address this problem, in this article, we present our literature review on evidence as to how a good knowledge of proper management among researchers can enhance the likelihood of the success of clinical trial projects.Evidence Acquisition:Using multiple search strategies, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 30 publications
0
12
0
7
Order By: Relevance
“…Research evidence has suggested that despite the importance of having a well-constructed protocol, success is enhanced by efficient management of research tasks, timelines and staff [ 10 ]. It is generally considered that approximately 50% of the total time spent on a study relates to its conduct, including recruitment of participants and collection and monitoring of data [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research evidence has suggested that despite the importance of having a well-constructed protocol, success is enhanced by efficient management of research tasks, timelines and staff [ 10 ]. It is generally considered that approximately 50% of the total time spent on a study relates to its conduct, including recruitment of participants and collection and monitoring of data [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Trial managers have to project confidence amongst other team members, be highly organised, communicate and coordinate effectively, have the ability to multi-task, think laterally and strategically and be motivational [ 4 ]. If the trial manager is performing successfully, enhancing communications and negotiations with significant contributors via an appropriate infrastructure [ 15 ], trial outcomes can be optimised [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested solutions to administrative/managerial barriers to research recruitment by adopting methodologies from business world and marketing, including elements such as building brand value, explicit marketing plan, signaling worthiness, making the sale and others (7). Future studies may need to test benefits of these methodologies for recruitment of practices especially from larger organizations.…”
Section: Discussionmentioning
confidence: 99%
“…While several studies identified some barriers to primary care physicians' recruitment and research participation (4,5), to date, evidence is limited to inform provider recruitment planning for primary care research projects (4). While many studies focus on the patient and provider recruitment in clinical trials (6,7), recruitment needs in primary care, however, go far beyond the scope of randomized clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, proper facilities, location, equipment, laboratory, product storage, and archive must be provided prior to study initiation [22,23].…”
Section: Quality Of Datamentioning
confidence: 99%